Theōria as Cure for Impiety and Atheism in Plato’s Laws and Clement of Alexandria - Anagnostou-Laoutides, Evangelia ca. 20./21. Jh. (Religions, 2024)
The article examines the impact of Plato’s views on atheism and impiety, relayed in the Laws, on Clement of Alexandria. Clement employed the adjectives godless (atheos) and impious (asebēs) often in his writings as accusations against pagan philosophers and/or heretics, but also in his defence of Christians against the very charge of atheism on account of their rejection of pagan gods (Stromata 7.1; cf. Tertullian’s Apologia 10). I argue that Clement, perceptive of Plato’s defence of philosophical contemplation (theōria) and its civic benefits in the Laws, reworked the latter’s association of disbelief with excessive confidence in fleshly pleasures (Leges 888A) in tandem with his stipulation of virtue as the civic goal of his ideal colonists of Magnesia who ought to attune to the divine principles of the cosmos. Thus, Clement promoted the concept of citizenship in the Heavenly kingdom, secured through contemplation and its ensuing impassibility. For Plato and Clement, atheism was the opposite of genuine engagement with divine truth and had no place in the ideal state. Although Clement associated the Church with peace, his views were adapted by Firmicus Maternus to sanction violent rhetoric against the pagans in the fourth century when Christianity became the official religion of the Roman Empire.